The translation of the Chinese dragon culturema into Spanish: evangelical adaptation in History of the Great Kingdom of China by Juan González de Mendoza - Gao, Bo (Estudios Complutenses de Asia Oriental, 2025)
For more than five centuries, the history of the Great Kingdom of China always has a significant cultural influence on scholars. However, most of them have overlooked the strategy adopted by González de Mendoza in translating some Chinese culturemes into Hispanic culture. Among other details, I have been particularly struck by the translation of the term "Chinese dragon", an exclusive symbol of authoritarian emperors in the Ming dynasty, where the author employed the word "serpent", a term that refers to a well-known animal in the Iberian Peninsula. This procedure represents a significant cultural clash, as the translation carries a completely different meaning, and thus unacceptable for traditional Chinese culture. Although some studies have perceived this incongruity, they have merely justified it, indicating the semantic difference of "dragon" in the two cultures. So far, there has been no clear explanation of the allegory of "serpent" in the contemporary Spanish context, nor have the reasons for the Augustunian's use of this adaptation been accurately identified. For this reason, our attention has focused on identifying the reasons that drove the author to apply this term, along with all its interpretations of its allegory in the sixteenth century. In the end, we have managed to discover the evangelical motivation that led to the adaptation strategy, which aligns with the purpose of this monumental work of the Golden Age.
Keywords: cultureme; cultural adaptation; dragon; Juan González de Mendoza; Ming dynasty